Key Competences Formation by Means of Learning Foreign Languages - M. A. Shemanaeva (Moscow Polytechnic University, 2018)
The shift of higher education system to the new federal state standards for education (FGOS3++) is connected with the changes in the curriculum and  terminological shift from so called general cultural competences to key competences. Key competences are the basis for professional competences and lay the foundation for further  personal and professional development of a specialist. Recent research in  teaching foreign languages in higher education institutions have been aimed at the development of professional competences. However the  empirical data show that first-year students of non-linguistic departments do  not have school level command of the foreign language. The article considers the potential of the foreign language to form not only communicative  competence in the foreign language but to form key competences,  mentioned in the new federal standard, regardless of the initial level of language competence.